Belief in a just world lowers perceived intention of corruption: the mediating role of perceived punishment - Bai, Bao-yu (2014)
Corruption can be unfair and detrimental to societies; however, little is known regarding how individuals perceive corruption. We aim to understand how psychological factors, such as lay belief of the world, influence perceived intention of corruptive behavior. As corruption undermines justice, we hypothesize that belief in a just world to others (BJW-others) reduces perceived intention of corruptive behaviors. We conducted two correlational studies and one experimental study in China. Using hypothetical scenarios, perception toward bribery taking and nepotistic practices were assessed. In Study 1 and Study 2, we consistently found that BJW-others negatively predicted perceived intention of corruption, and this pattern was mediated by perceived likelihood of punishment. We further replicate this result in Study 3 by priming BJW-others, demonstrating its causal effect. The results indicate that BJW as one lay belief can be important in influencing people’s attitudes toward corruption. Implications for future research and anti-corruption policies are also discussed.